The Monarchia controversy : an historical study with accompanying translations of Dante Alighieri's Monarchia, Guido Vernani's Refutation of the Monarchia composed by Dante and Pope John XXII's bull, Si fratrum - Cassell, Anthony K. (Anthony Kimber), 1941-2005 (Catholic University of America Press, 2004)
"The Monarchia Controversy provides both the background to the imperial and ecclesiastical machinations that drove Dante Alighieri to begin penning the Monarchia in 1318 and also the subsequent history of the efforts by papal authorities to ban the book after the writer's death. Dante's political treatise on the Empire and the Papacy was listed by the Church in the Index Librorum Prohibitorum in 1564, and it was removed only in 1881. Anthony Cassell's account of the Monarchia's genesis is both compelling and provoking, especially in the descriptions of the intransigence of Dante's proponents and antagonists.